Characterization of the erythromycin degradation pathway and related enzyme in Rhodococcus gordoniae rjjtx-2. (15th December 2022) - Ren, Jianjun; Ni, Shensheng; Shen, Yunpeng; Niu, Dongze; Sun, Rumeng; Wang, Chongqing; Deng, Liujie; Zhang, Qiaopan; Tang, Yue; Jiang, Xingmei; Li, Zhijie; Li, Chunyu
Abstract: The persistence and ecotoxicity of erythromycin residues pose a severe risk to the environment and human beings. Biodegradation is an efficient and economical process to remove residual erythromycin from the environment. In this study, a novel erythromycin-degrading bacterium rjjtx-2 was isolated and identified as Rhodococcus gordoniae rjjtx-2 based on its morphology and phylogenetic analysis of the 16S rRNA gene sequence (Accession No. OK039192). The optimal erythromycin-degrading conditions for the strain rjjtx-2 were 35 °C and pH 7.0 with 100 mg L −1 erythromycin, resulting in a maximum degradation rate of 75% after 72 h incubation. Moreover, HPLC-MS identified four intermediates (C37 H65 NO12, C29 H51 NO9, C29 H53 NO10, and C21 H34 O6 ). Based on intermediates and enzymatic analyses, erythromycin was speculated to be converted into C21 H34 O6 through cleavage of the lactone ring by an erythromycin-degrading esterase and the decrease of cladinose and desosamine by glycoside hydrolases. Finally, the degradation enzyme EreA was cloned and expressed, and we predicted the three-dimensional structure of the erythromycin-binding and catalytic residues (E37, H40, E68, R251, D252, and H279). This study reveals that R . gordoniae rjjtx-2 is a promising bacterium for remediation in erythromycin contaminated environments. Graphical abstract: Image 1 Highlights: A novel erythromycin-degrading strain Rhodococcus gordoniae rjjtx-2 was isolated from an erythromycin-contaminated sample. The erythromycin degradation pathway of R. gordoniae rjjtx-2 was illustrated. The esterase and glucoside hydrolase are the key enzymes involved the biodegradation process. The erythromycin esterase EreA was cloned, and the three-dimensional model of EreA binding erythromycin was predicted.